The Goal of Housing for All As Envisaged By the UN Habitat Agenda: A Case Study of Cooperative Housing Societies in Pakistan - Nawaz, Hafiz Muhammad Usman; Baig, Mirza Shahid Rizwan; Idrees, Dr. Rao Qasim (Journal of Peace, Development and Communication, 2021)
Pakistan is member of UN Habitat agenda under which housing for all is the goal of all member states. In pursuance of this goal housing has been acknowledged under the Constitution of Islamic Republic of Pakistan 1973 in the chapter of principles of policy. It is beyond of financial resources of the Government of Pakistan to provide housing units to all the citizens of Pakistan. To achieve the goal of housing for all, private sector has been encouraged to provide housing units to the people of Pakistan. But, due to a weak Legal Framework to regulate the activities of the developers of the housing industry, there are malpractices and frauds in the housing industry of Pakistan which are committed by the management of the cooperative housing societies. This article deals with the major problems faced by the cooperative housing societies along with the recommendations to strengthen the Legal Framework relating to cooperative housing societies. Secondary data has been used to make critical analysis of the regulatory regime of cooperative housing societies. The aims and purposes of this article includes to provide input the legislature as well as regulatory authorities to amend and strengthen the Legal Framework relating to cooperative housing societies in Pakistan.